Elaboración y aplicación de guía didáctica con enfoque constructivista para el aprendizaje de trigonometría en los estudiantes de tercer semestre, de la escuela Ciencias Exactas, periodo diciembre 2012 – junio 2013. - Cruz Morocho, María Inés (2016)
It has been seen over experience as a teacher that, while it is true the Trigonometry as such is an important branch that involves understanding the issues that surround us: but before the students, teachers have been using the method of traditional teaching, where it only dictates the theoretical class and resolves the exercises in the Blackboard, as soon as the student there are times that learn and there are times that are empty in relation to the understanding of trigonometry. Leading the student to be lost in the teaching-learning process giving birth to many negative effects not only in the teaching-learning process but also on a personal level, producing a denial to study and understand the trigonometry, the solution to this problem is the development and implementation of an instructional guide with a constructivist approach based on the syllabus of the third semester of exact sciences, being one of the best strategies to ensure the acquisition of the trigonometric knowledge. For its development the inductive, analytical and synthetic research methods w ere used; the type of research in which it was sustained and based is the diagnostic or proactive research, the same that has a field design, bibliographic. In addition, the research was supported by the validation of an instrument to collect information such as the survey and questionnaire, which were applied to seventeen male students, which demonstrate that for the teaching-learning process be complete, dynamic and fun should be applied the implementation of an instructional guide with thematic contents according to the trigonometry syllabus of the third semester and its application in the resolution of problems taking the active involvement of students completing the teaching process with a meaningful learning.